Gamma-Induced Transformations in PVC-Based Nanocomposites for Tailored Optical Properties - Badriah Alshahrani; Ahmed Hassan Korna; Soad Saad Fares; Ahmed H. Ali (International Journal of Polymer Science)
This study explores the effects of gamma irradiation on the properties of polyvinyl chloride (PVC):(50 nm)/CeO2:(10 nm)/TiO2 nanocomposite films. Gamma irradiation significantly enhances the optical conductivity (σopt) of the films, signifying increased light-to-current conversion efficiency. This improvement is attributed to a reduction in the bandgap and increased light absorption induced by irradiation. X-ray diffraction (XRD) analysis reveals a decrease in crystallinity due to disrupted atomic order within the nanocomposite. Williamson–Hall (W-H) plots show a dose-dependent reduction in crystallite size and a corresponding rise in lattice strain with increasing irradiation dose. Infrared (IR) spectroscopy suggests potential bond breaking of O-H groups and modifications in C=O functional groups upon irradiation. The absorption coefficient and binding energy exhibit a nonmonotonic response with increasing dose, reaching an optimum at around 100 kGy. These findings demonstrate the potential of gamma irradiation for tailoring the optoelectronic properties of PVC:(50 nm)/CeO2:(10 nm)/TiO2 nanocomposites. This work paves the way for the development of next-generation optoelectronic devices with optimized functionalities.